2013
DOI: 10.1074/jbc.m112.431346
|View full text |Cite
|
Sign up to set email alerts
|

Unique Features of the Anti-parallel, Heterodimeric Coiled-coil Interaction between Methyl-cytosine Binding Domain 2 (MBD2) Homologues and GATA Zinc Finger Domain Containing 2A (GATAD2A/p66α)

Abstract: Background:The MBD2-p66␣ coiled-coil interaction is key to the function of the NuRD chromatin remodeling complex. Results: Binding to p66␣ depends on helicity and electrostatic potential of the MBD2 domain. Conclusion: Variations in helical content and charge distribution dictate a binding affinity hierarchy for MBD2 homologues. Significance: Delineating determinants of binding will aid the development of inhibitors of these complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 37 publications
(41 reference statements)
3
39
0
Order By: Relevance
“…We previously biophysically characterized and determined the structure of a coiled-coil complex formed between vertebrate MBD2 and GATAD2A (p66α), and showed that this interaction was critical for recruitment of CHD4 and methylation-dependent gene silencing by NuRD3435. In the current studies we tested whether the invertebrate coiled-coiled domains from EmMBD2/3 and EmGATAD2A/B could form a similar stable coiled-coil complex.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…We previously biophysically characterized and determined the structure of a coiled-coil complex formed between vertebrate MBD2 and GATAD2A (p66α), and showed that this interaction was critical for recruitment of CHD4 and methylation-dependent gene silencing by NuRD3435. In the current studies we tested whether the invertebrate coiled-coiled domains from EmMBD2/3 and EmGATAD2A/B could form a similar stable coiled-coil complex.…”
Section: Resultsmentioning
confidence: 92%
“…5b), residues involved in direct contact between the two proteins are highly conserved. We previously identified three intermolecular ionic/hydrogen bond interactions critical for high affinity binding3435. The equivalent interactions are maintained in the E. muelleri complex (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…We also generated a construct, MBD3cc, consisting of murine MBD3 fused to residues 133–174 of mouse GATA2DA (UniProt ID: Q8CHY6 ). This region of GATA2DA has been previously shown to form a coiled-coil interaction with MBD3 [42]. We hypothesised that fusing this region of GATA2DA to MBD3 could stabilise and improve expression of MBD3.…”
Section: Methodsmentioning
confidence: 98%
“…Histone-binding proteins Rbbp7 and Rbbp4 (RbAp46 and RbAp48, respectively) bind histone H4 and are thought to function as scaffolding proteins or chaperones which coordinate assembly of multi-protein complexes [25]. Nuclear zinc-finger protein Gata2a and Gata2b (p66α/β) directly interact with MBD2/3 via a coiled-coiled antiparallel interface [26, 27]. While HDAC1/2 and Rbbp7/4 are present in other histone deacetylase co-repressor complexes, such as SIN3 and coREST [28, 29], Mi2, MBD3 and MTA are relatively specific to NuRD and thought to be defining components of this complex.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, development of chemical inhibitors based on this structural information could in principal be tested to treat hemoglobinopathies. The p66α coiled-coil peptide has a similar affinity for MBD3, suggesting that this strategy could also be used to target MBD3-containing NuRD complexes [27]. …”
Section: Introductionmentioning
confidence: 99%